El mercurio y la producción minera en la Nueva España, 1810-1821 - Romero Sotelo, María Eugenia (El Colegio de México, A.C., 2000)
This work presents results of research on financing, transportation and allotment of quicksilver in New Spain's mining industry during 1810-1821. The author points out that the  war of lndependence was the main cause of the mining crisis, describes the effect of this conflict on production organization and distribution of colonial silver industry, and claims that one of the strongest blows on mining was the Spanish government's credit with drawal. Furthermore, the study offers data on amounts of mercury available for mining, costs of its transportation, and details of its allotment and distribution to royal mines.